PROSES DEMOKRASI DESA DAN STRATEGI PEMENANGAN BERBASIS BUDAYA JAWA DI PILKADES DESA TANJUNG KECAMATAN PAGU KABUPATEN KEDIRI - Endik Hidayat; Miskan (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
Implementationof Law No. 6 of 2014 concerning Villages, regulating the election of village heads simultaneously. In contrast to most post-reform studies in 1998 which analyzed village head election with a material approach or money politics. Instead this study elaborates on political strategy from the perspective of Javanese culture in village political contestation. The study begins identifying who the candidates who fought in Tanjung village head election, the extent to which a cultural approach through the idea of Javanese power effectively won the election of village heads so that research could add a variety of political strategy models to village head election and become role models in rural democracy. With qualitative methods and take case studies of Tanjung village, Pagu District, Kediri Regency. The study identified who were the candidates who fought in PilkadesTanjung village, and the extent to which spiritual resources through the idea of Javanese power and material resources effectively won the village heads election. This study concluded that all candidates for Tanjung village head using a Javanese culture-based political strategy originated from a source of spiritual power whose variation was divided into six categories: first, the Slametan ceremony at the tomb of the village founder. Secondly, pitou services come from kiai and dukun. Third, ownership of heirlooms. Fourth, pulung as a sign of power. Fifth, petungan to the Java calendar system. Sixth,luri lineage village head